Oficina de saberes: uma intervenção pedagógica para além dos muros da escola: abordagem de oficinas nas comunidades de periferias - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present work of course completion, brings an approach in a succinct way, about teaching’s possibilities that meet the students necessity currently, especially concerning the peripheral communities, where the uninterest for the continuity in school education, rooted remaining as a sad cultural condition. From these reflections, we pursuit to present a teaching methodology that enables the construction of significant learning where the students act as protagonists in the knowledge's process acquisition, distancing itself from the model on which the teacher is the issuer and the student is the receiver. Aiming, especially, at the active participation, the young as protagonists, the dropout’s reduction and an environment that provides new life perspectives from the motivation to continue the education, that goes beyond basic education and enable the perception of studies importance for social ascension. Always encouraging the education's construction that reflects positively besides the school walls.
Keywords: Inclusão social; Educação; Oficinas de ensino; Prática pedagógica; Social inclusion; Education; Teaching workshops; Pedagogical practice; CNPQ::LINGUISTICA, LETRAS E ARTES